Optimization of Minimum Segment Width Parameter in the Intensity-Modulated Radiotherapy Plan for Esophageal Cancer - Hong J; Han JH; Luo HL; Song YQ (International Journal of General Medicine, 2021)
Jun Hong,* Ji-Hua Han,* Hong-Lei Luo, Ya-Qi Song Department of Radiation Oncology, The Affiliated Huaian No.1 People’s Hospital of Nanjing Medical University, Jiangsu, Huai’an, 223300, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ya-Qi Song; Hong-Lei LuoDepartment of Radiation Oncology, The Affiliated Huaian No.1 People’s Hospital of Nanjing Medical University, Jiangsu, Huai’an, 223300, People’s Republic of ChinaTel +86 18912089369Email songyaqi@111.com; luohonglei07@outlook.comPurpose: This study was designed to explore the optimal minimum segment width (MSW) in the intensity-modulated radiotherapy (IMRT) plan for esophageal cancer.Patients and Methods: The imaging data of 20 esophageal cancer patients were selected for this study. Four IMRT plans were designed for each patient with MSWs of 0.5, 1.0, 1.5, and 2.0 cm. The conformity index (CI) and homogeneity index (HI) of the planning target volumes (PTV), organs at risk (OARs), control points (CP), monitor units (MU), plan delivery time (DT), and gamma passing rates (GPR) were collected and compared to appraise the treatment plan quality and delivery efficiency.Results: Lower-MSW plans had larger CI and smaller HI values, and lower dose parameters of OARs and PTVs. The HI, CI, and dose parameter of OARs in the 0.5 and 1.0 cm MSW groups were similar and much better than those of the 1.5 and 2.0 cm MSW groups. Meanwhile, the plan in the 0.5 cm MSW group had significantly higher MUs, CPs, and DTs, and a significantly lower relative dose of GPR with a 3% dose difference and 3 mm distance to agreement criteria than the other three groups.Conclusion: The 0.5 and 1 cm MSW groups had better dosimetric parameters and IMRT plan quality than the other groups. However, plans with 0.5 cm MSW had worse delivery accuracy and efficiency than the other three groups. Thus, MSW of 1.0 cm was the optimal choice to ensure good quality, delivery accuracy, and treatment efficiency in IMRT plans for esophageal cancer.Keywords: esophageal cancer, minimum segment width, delivery efficiency, plan quality, intensity-modulated radiotherapy